Salve o povo que assim te quis - Morais, Igor Bernardes Cabral de (2016)
This dissertation is formed by two distinct pieces: the novel Salve o Povo que Assim te Quis (Hail the People who Willed you So in a literal translation), and an essay that analyses the writing process of it since its motivations – with great emphasis on the city of Brasília, local of the action and character of the story –, until the posterior impressions of its first readers and also of its author about the work.